2021
DOI: 10.3168/jds.2021-20680
|View full text |Cite
|
Sign up to set email alerts
|

Feeding milk supplemented with Ulva sp., Ascophyllum nodosum, or Saccharina latissima to preweaning dairy calves: Effects on growth, gut microbiota, gut histomorphology, and short-chain fatty acids in digesta

Abstract: Emerging knowledge shows the importance of preweaning nutrition on programming the gastrointestinal microbiome and development of the gut barrier function. The aim of this study was to assess the effects of supplementing cow milk with either intact dried Ulva sp., Ascophyllum nodosum, or Saccharina latissima on growth performance and several gut health parameters of preweaning dairy calves. Forty male Holstein calves were selected based on birth weight (41 ± 4 kg) and plasma Brix percentage (≥8.7%) at d 2 of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Of the faecal fermentative end-products, acetic acid was most likely affected by the total dietary fibre content of the treatments (TDF CTR diet = 11.75%; TDF HP diet = 12.92%; TDF HPA diet = 18.02%), being the lowest in the CTR group, and peaking after HPA dietary intervention, where it reached statistical significance. It can be conjectured that the present finding reflected the inclusion of AN, a rich source of soluble fibres (e.g., alginic acid, laminarin, and sulphated polysaccharides) [ 12 ] in the HP diet, which stimulated acetogenesis within the gut microbiota, as already reported in humans and pre-ruminants [ 64 , 65 ]. In sharp contrast, a recent investigation carried out in healthy dogs failed to demonstrate any influence on faecal L-SCFA profile when intact AN was supplemented at a dose of 15 g/kg of diet (as is) for a maximum of 28 days [ 66 ].…”
Section: Discussionsupporting
confidence: 56%
“…Of the faecal fermentative end-products, acetic acid was most likely affected by the total dietary fibre content of the treatments (TDF CTR diet = 11.75%; TDF HP diet = 12.92%; TDF HPA diet = 18.02%), being the lowest in the CTR group, and peaking after HPA dietary intervention, where it reached statistical significance. It can be conjectured that the present finding reflected the inclusion of AN, a rich source of soluble fibres (e.g., alginic acid, laminarin, and sulphated polysaccharides) [ 12 ] in the HP diet, which stimulated acetogenesis within the gut microbiota, as already reported in humans and pre-ruminants [ 64 , 65 ]. In sharp contrast, a recent investigation carried out in healthy dogs failed to demonstrate any influence on faecal L-SCFA profile when intact AN was supplemented at a dose of 15 g/kg of diet (as is) for a maximum of 28 days [ 66 ].…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, the SCFA content in feces is related to some diseases such as irritable bowel syndrome (IBS), cardiovascular diseases, diarrhea [39], and cancer [40]. At the same time, previous studies have shown that SCFAs can regulate the host's biological response, including intestinal integrity, lipid metabolism, and the immune system [41][42][43][44][45]. Butyrate is the main energy source of colon epithelial cells, which can reduce the permeability of intestinal mucosa, promote the recovery of the intestinal barrier, and prevent or reduce the incidence of colon cancer [46].…”
Section: Discussionmentioning
confidence: 99%
“…However, extracts from these seaweeds have been reported to be used in feeding farm animals. Samarasinghe et al 14 have reported the effects of milk supplementation with Ulva sp. fed to preweaning calves on performance and gut health.…”
Section: Introductionmentioning
confidence: 99%